Reducing Residential Energy Demand through Optimal Roof Insulation Practices: Insights from Lahore, Pakistan - Beenish Mujahid,; Dr.Tauseef Ahmed,; Seemin Aslam,; Arsala Hashmi, (Dialogue Social Science Review (DSSR), 2025)
This research quantifies the impact of roof thermal insulation in reducing residential energy demand in Lahore, Pakistan. Using Autodesk Revit BIM software, energy analysis was conducted on a contemporary two-story residential building, testing various insulation materials to determine their effectiveness in reducing cooling demands during summer. The influence of insulation thickness was also evaluated. Results indicated that applying 2-inch-thick insulation could reduce building cooling load demand by approximately 25%. The study concludes that significant energy savings can be achieved if the Pakistani government actively promotes the application of insulation materials in both existing and new residential buildings. Keywords: Cooling Load, Energy Consumption, Insulation Materials, Roof Insulation, R-value, Sustainable Design.